Perkembangan Sistem Sanitasi pada Rumah Tradisional Bugis di Sulawesi Selatan - Iskandar; Muhammad Ardi; Nurlita Pertiwi (SEMINAR NASIONAL DIES NATALIS 62, 2023)
The architecture of the Bugis residence is one of the cultural elements that grows and develops in South Sulawesi Province. The Bugis community that builds houses on stilts influences the condition of the surrounding environment. This article describes the development of sanitation systems with an increase in community environmental knowledge. This study is qualitative in nature with data collection methods through observation of traditional houses in Sidenreng Rappang Regency. The focus of this study is the clean water and dirty water management system. The results of this study found that the environmental sanitation system in traditional Bugis homes develops according to the needs and knowledge of the community and contributes to creating environmental quality.